Immediate Agreement in Interdependent Bilateral Bargaining - Jonas Björnerstedt; Johan Stennek (Research Institute of Industrial Economics (IFN), 2007)
This note provides sufficient conditions for immediate agreement in an extensive form model of interdependent bilateral bargaining. The model is suggested by Björnerstedt and Stennek (2006) as a work horse for studying bilateral oligopoly. The key feature of this model is that the firms are represented by separate agents in all negotiations in which they are involved. There is immediate agreement in equilibrium, essentially if production is strictly convex or if the agents use Markov strategies.
Keywords: C70; D20; D40; L10; L40; 330; Bilateral Oligopoly; Intermediate Goods; Bargaining; Market Network; Trade Link; Spieltheorie; Verhandlungstheorie; Oligopol; Vorprodukt; Unternehmensnetzwerk